2014
DOI: 10.5897/jmpr2014.5500
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of tannins from Psidium guineense Sw. (Myrtaceae)

Abstract: The aim of this study was to quantify and evaluate the antibacterial activity of tannins extracted from leaves of Psidium guineense, obtained using two different isolation methods, against Staphylococcus aureus and Pseudomonas aeruginosa. The first extraction method was used to isolate condensed tannins (Method A) and the second to isolate mixtures rich in esters of gallic acid and glucose (Method B). Both extraction methods yielded high concentrations of tannins, with 312 and 257 mg/g of dry material obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
15
0
2
Order By: Relevance
“…A preliminary phytochemical analysis can identify the relevant metabolite groups that may be related to the identified biological activities, thus guiding the research to obtain an effective and safe herbal medicine, in addition to identifying possible toxic active ingredients (Cragg and Newman, 2013). Previous phytochemical researches with the plant species in this study confirm the results found in the phytochemical analysis like antibacterial activity (Al-Mariri and Mazen, 2014;Rodrigues et al, 2014;Tankeo et al, 2016). Ferreira (2005) while studying the anti-ulcerogenic activity of A. humile, detected the presence of tannins and flavonoids.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A preliminary phytochemical analysis can identify the relevant metabolite groups that may be related to the identified biological activities, thus guiding the research to obtain an effective and safe herbal medicine, in addition to identifying possible toxic active ingredients (Cragg and Newman, 2013). Previous phytochemical researches with the plant species in this study confirm the results found in the phytochemical analysis like antibacterial activity (Al-Mariri and Mazen, 2014;Rodrigues et al, 2014;Tankeo et al, 2016). Ferreira (2005) while studying the anti-ulcerogenic activity of A. humile, detected the presence of tannins and flavonoids.…”
Section: Discussionsupporting
confidence: 78%
“…Lignins and tannins were isolated from M. urundeuva by Morais et al (1999) and Queiroz et al (2002). Vergas et al (2007) and Rodrigues et al (2014) reported the presence of tannins in leaves from plants of the genus Psidium.…”
Section: Discussionmentioning
confidence: 99%
“…Capparis spinosa L. is one of many medicinal plants that has therapeutic value because presence of different active chemical compounds in its various parts [26,27,28] ., the active lipids were isolated from Capparis spinosa L. buds by using continuous extraction depending on hexane as a solvent . The weight of lipids was 1.6 gm and the extraction percentage was 3.2% as in table (1). This extraction percentage is considered somewhat small compared to another percentage of alkaloid compounds isolated from the same parts of Capparis spinosa L. [20] .…”
Section: Discussionmentioning
confidence: 99%
“…These medicinal plants have many active chemical compounds as secondary metabolites resulting from secondary metabolism pathways and these compounds have various active functional groups in their chemical structures [1,2] . The active chemical compounds existing in different parts of medicinal plants are phenolic compounds, flavonoids, tannins, alkaloids, glycosides, essential oils and steroids, so the presence of these secondary metabolites in plant give the medicinal and biochemical action of these plants to treat various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory action could be attributed to the tannins and flavonoids, since these constituents are well established as antimicrobial agents (Nenaah, 2013;Aguilar-Galvez et al, 2014;Bagla et al, 2014;Rodrigues et al, 2014;Zhang, Wang & Xu, 2014) and, they are present in the infusion and macerated extracts.…”
Section: Discussionmentioning
confidence: 99%